THE RELATIONSHIP BETWEEN AUDITORY LEARNING STYLES AND PEER INTERACTIONS WITH MATHEMATICS LEARNING INTEREST SMAS STUDENTS HOPE STEM ATTACKS - Eka Puji Safitri; Hasanuddin; Suaidah Lubis (RADJA PUBLIKA, 2023)
To improve student learning achievement, a solution is needed that can increase enthusiasm and foster student interest in learning while in class to participate in teaching and learning activities and can influence students in obtaining satisfactory results. One solution that can be done to overcome the problems that have been identified is to use external factors, namely peer interaction and internal factors which include factors that exist in students, namely students' auditory learning styles. This study aims to analyze and determine the relationship between auditory learning style and peer interaction with the learning interests of Harapan Batang Serangan Private High School students. This research belongs to the type of quantitative research, the method used is descriptive correlational type. The research sample was 183 students of class X and XI of Batang Serangan Private High School. Research data was collected using a research scale that was declared valid and reliable. The data analysis technique uses two predictor regression analysis. The results showed that: (1) there is a significant relationship between auditory learning style and learning interest, with a probability value of 0.03 <0.05; (2) there is no significant relationship between peer interaction and learning interest, with a probability value of 0.06 <0.05; (3) there is a significant relationship between auditory learning style and peer interaction with interest in learning mathematics at Harapan Batang Serangan Private High School, with a probability value of 0.04 <0.05.